Managing Global Warming : an Interface of Technology and Human Issues - Letcher, T. M. (Trevor M.) (Academic Press, 2018)
What are the causes of global warming? What options are available to solving the global warming problem? How can each option be realistically implemented? Technological Solutions to Global Warming is the first book of its kind, based on scientific content providing an overall reference looking at the problems of global warming and possible solutions in one volume. Containing all the necessary authoritative chapters written by scientists and engineers working in the field; each chapter includes the very latest research and references in the potential impact of wind, solar, hydro, geo-engineering and other energy technologies on climate change. With such a wide ranging set of topics and solutions readers will find a beneficial synergy, between the different solutions and issues, making this a handbook for engineers, professors, leaders and policy makers.